1999
DOI: 10.1046/j.1462-2920.1999.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The generation of multiple co‐existing mal‐regulatory mutations through polygenic evolution in glucose‐limited populations of Escherichia coli

Abstract: The multicomponent glucose transport system of Escherichia coli was used to study the polygenic basis of increased fitness in prolonged nutrient-limited, continuous cultures. After 280 generations of glucose-limited growth, nearly all bacteria in four independent chemostat populations exhibited increased glucose transport and contained multiple, stable mutations. Fitter bacteria increased outer membrane permeability for glucose through overexpression of the LamB glycoporin. Three classes of mutation influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
106
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 46 publications
(88 reference statements)
12
106
0
Order By: Relevance
“…This group of genes has already been identified as involved in adaptation to a better glucose uptake rate in other evolution experiments. For example, in all replicate populations of a 280-generation experiment performed under continuous growth (chemostat culture) on glucose, the mal/lamB genes were found overexpressed, leading to a significant increase in glucose uptake (Notley-McRobb and Ferenci 1999;see Kurlandzka et al 1991 for other examples). This improvement is probably linked to the LamB protein, known as being the most important contributor to glucose uptake under nutrient limitation (Death et al 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of genes has already been identified as involved in adaptation to a better glucose uptake rate in other evolution experiments. For example, in all replicate populations of a 280-generation experiment performed under continuous growth (chemostat culture) on glucose, the mal/lamB genes were found overexpressed, leading to a significant increase in glucose uptake (Notley-McRobb and Ferenci 1999;see Kurlandzka et al 1991 for other examples). This improvement is probably linked to the LamB protein, known as being the most important contributor to glucose uptake under nutrient limitation (Death et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Classic genetic and physiological microbial models, such as yeast and bacteria, offer a powerful alternative. By coupling evolution experiments and genetic investigations in these microorganisms, several studies have identified cellular functions involved in evolutionary processes (e.g., Treves et al 1998;Notley-McRobb and Ferenci 1999;Cooper et al 2001;Spencer et al 2007). However, in most of the cases, these studies focus on specific candidate genes, and general investigations of metabolic changes are rare (but see Kurlandzka et al 1991;Cooper et al 2003;Pelosi et al 2006).…”
mentioning
confidence: 99%
“…(v) Phenotypes 3, 4 and 5 are generated from phenotype 2, 3 and 4, respectively, in the same way. It should be noted that we use the term phenotype here not for a cell line carrying a defined mutation but for a group of different mutants that have the same improved kinetic properties with respect to µ max and K s on glucose [compare with Notley-McRobb & Ferenci (2000, 1999a]. This process is illustrated in Fig.…”
Section: Modelmentioning
confidence: 99%
“…Notley-McRobb & Ferenci (2000) estimated that in their glucose-limited chemostats (Dl 0n3 h −" ), containing 2-3i10"! cells in total, 10% mutants with an improved glucose affinity were generated at each replication round due to loss-of-function mutations in mgl and mlc.…”
Section: Effects Of Monod Kinetics On Population Dynamicsmentioning
confidence: 99%
“…According to citations, this transposable reporter construct has been used in more than 100 studies of gene regulation but has not been fully sequenced. placMu50 was introduced into MC4100 to generate MC4100(MuLac) strain BW2952, the ancestor strain in experimental evolution experiments, because mal expression is a useful marker for detecting an assortment of regulatory mutations in evolving cultures (9,23).…”
mentioning
confidence: 99%